Anti-cyclic citrullinated peptide antibodies in patients with sarcoidosis - Kobak, Senol; Ylmaz, H.; Sever, F.; Duran, A.; Sen, N. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Introduction: Anti-cyclic citrullinated peptide (anti-CCP) antibodies have a high predictive value in rheumatoid arthritis (RA) patients and are associated with disease severity. Sarcoidosis is a chronic inflammatory disease characterized by non-calcified granuloma formations. Aim: To determining the prevalence of anti-CCP antibodies in patients with sarcoidosis, and identifying a possible correlation with clinical and laboratory findings. Materials and Methods: Forty-two patients presenting to the rheumatology polyclinic and diagnosed with sarcoidosis as a result of the examinations made, 45 RA patients and 45 healthy subjects were included in the study. Demographic, clinical, serological and radiological data of all patients were recorded. Anti-CCP antibodies were evaluated by using a second-generation ELISA method. Rheumatoid factor (RF) IgM was determined with the nephelometry method. Results: Forty-two patients (10 males) were included in the study. Mean patient age was 45.2 years (20-70 years) and mean duration of disease was 3.5 years. Two sarcoidosis patients (4.7%) and 38(84.4%) RA patients were found to be positive for anti-CCP antibodies while the antibody wasn’t detected in any healthy subject. The two sarcoidosis patients found positive for anti-CCP were also diagnosed with rheumatoid arthritis. RF positivity was detected in 7 sarcoidosis patients (16.6%) and in only one subject in the control group. Conclusion: The prevalence of anti-CCP antibodies in patients with sarcoidosis was found to be significantly lower than RA patients and similar with the healthy control group. This result shows that anti-CCP antibodies don’t have an important role in the pathogenesis of sarcoidosis, but could be important in revealing the overlap syndromes of sarcoidosis-RA